Peculiarities of Implementing the State's Strategic Narrative based on the Public Opinion - Voitko, Oleksandr; Loza, Volodymyr; Khudov, Hennadii; Bakhvalov, Valentyn; Chernozubkin, Igor; Kuchuk, Nina; Oleksenko, Oleksandr; Chepel, Maksym; Khizhnyak, Irina; Yuzova, Iryna; Чернозубкін, Ігор Олександрович; Chernozubkin, Igor (IJETAE Publication House, 2021)
The main purpose of the article is the peculiarities of implementing of the state's strategic narrative based on the the statistical analysis of the public opinion. The scenarios of the public opinion development are forecasted. The main results are: the graphs of the statistical series of change in public opinion have been constructed; the approximating functions for the trend of change in public opinion have been determined; the parameters of the approximating function have been calculated; a point forecast of the change in public opinion has been made. The main scientific method ia the method of statistical extrapolation. The main results are: to identify the features of the implementation of the strategic narrative of the state system in strategic communications; it is obtained the necessary minimum value of efficiency. This value of efficienct should be achieved by the system of strategic communications, when taking appropriate measures to promote and support of the appropriate course of the state by the population. This result is actually such as in the controlled territory and in the temporarily occupied territories (Donetsk and Luhansk regions, the Crimea).
Keywords: informational and psychological influence; strategic communications; strategic narrativ; target audience